Exploring performance limits of a new martensitic high strength steel by ausforming via equal channel angular pressing. (15th July 2020) - Vaughan, M.W.; Samimi, P.; Gibbons, S.L.; Abrahams, R.A.; Harris, R.C.; Barber, R.E.; Karaman, I.
Abstract: Strength and toughness limits of a newly developed low alloy martensitic steel are explored using impact toughness experiments and room temperature tensile testing. These steel samples are subjected to either a selected heat treatment, to obtain tempered martensite, or equal channel angular pressing (ECAP) performed between 950 °C and 1050 °C, to refine prior austenite grains. Martensite refinement through ECAP led to a significantly enhanced mechanical response, resulting in impact toughness above 55 J at -40 °C and ultimate tensile strengths above 2 GPa at room temperature. Consequently, this new low alloy steel can be an excellent candidate for high specific strength transportation applications. Graphical abstract: Image, graphical abstract